Intravenous versus oral rehydration in athletes - van Rosendal, S. P.; Osborne, M. A.; Fassett, R. G.; Lancashire, B.; Coombes, J. S. (Sports Medicine, 2010)
Fluid is typically administered via intravenous (IV) infusion to athletes who develop clinical symptoms of heat illness, based on the perception that dehydration is a primary factor contributing to the condition. However, other athletes also voluntarily rehydrate with IV fluid as opposed to, or in conjunction with, oral rehydration. The voluntary use of IV fluids to accelerate rehydration in dehydrated, though otherwise healthy athletes, has recently been banned by the World Anti-Doping Agency. However, the technique remains appealing to many athletes. Given that it now violates the Anti-Doping Code, it is important to determine whether potential benefits of using this technique outweigh the risks involved. Several studies have shown that rehydration is more rapid with IV fluid. However, the benefits are generally transient and only small differences to markers of hydration status are seen when comparing IV and oral rehydration. Furthermore, several studies have shown improvements in cardiovascular function and thermoregulation with IV fluid, while others have indicated that oral fluid is superior. Subsequent exercise performance has not been improved to a greater extent with one technique over the other. The paucity of definitive findings is probably related to the small number of studies investigating these variables and the vast differences in the designs of studies that have been conducted. The major limitation of IV rehydration is that it bypasses oropharyngeal stimulation, which has an influence on factors such as thirst sensation, antidiuretic hormone (arginine vasopressin) release, cutaneous vasodilation and mean arterial pressure. Further research is necessary to determine the relative benefits of oral and IV rehydration for athletes.